The makings of maleness: towards an integrated view of male sexual development - Wilhelm, Dagmar; Koopman, Peter (Nature reviews. Genetics, 2006)
Key Points The correct development of two distinct sexes from a sexually undifferentiated, bipotential embryo is a multi-step process that is essential for mammalian reproduction. Disorders of sexual development in humans are surprisingly common, but most remain unexplained at the molecular level. In mammals, male development is initiated by the expression of the male-determining Y-chromosomal gene Sry in the bipotential genital ridge, resulting in the differentiation of Sertoli cells. These in turn orchestrate the differentiation of all other cell types in the developing testes. Hormones produced by the testes influence the development of other male sexual characteristics: anti-Müllerian hormone results in the degeneration of the female-specific Müllerian duct, insulin-like 3 hormone is responsible for testicular descent, and androgens control the male-specific differentiation of the genital tract, prostate, external genitalia and brain. In addition to steroid hormones, a specific set of genes is required for each differentiation step. These sets of genes build a network of gene regulation and signal-transduction pathways, which involves a common series of 'hub' genes that are important for most, if not all, processes, in addition to tissue-specific genes. Evidence exists that Sry and/or other genes are directly involved in sexual dimorphism of the brain. Further work is required to unravel the broader spectrum of events that are involved in male development, moving beyond the issue of how testes differentiate. Included in this is the challenge to resolve the mechanisms that drive the coordination and integration of the different systems (testes, genital tract, accessory organs, external genitalia and brain) that contribute to normal male anatomy and physiology. In mammals, the SRY protein initiates the male developmental programme. This begins with testis determination and is followed by a network of transcriptional and endocrine signalling events in other organs. The authors review our current understanding of this process. As the mammalian embryo develops, it must engage one of the two distinct programmes of gene activity, morphogenesis and organogenesis that characterize males and females. In males, sexual development hinges on testis determination and differentiation, but also involves many coordinated transcriptional, signalling and endocrine networks that underpin the masculinization of other organs and tissues, including the brain. Here we bring together current knowledge about these networks, identify gaps in the overall picture, and highlight the known defects that lead to disorders of male sexual development.